Maternal Serum Lipid Trajectories and Association with Pregnancy Loss and Length of Gestation - Grantz, Katherine L.; Elmi, Angelo; Pugh, Sarah J.; Catov, Janet; Sjaarda, Lindsey; Albert, Paul S. (American Journal of Perinatology, 2020)
Objective We characterized lipid trajectories and investigated lipids and rate of pregnancy lipid change with the risk of pregnancy loss or preterm delivery <37 weeks.Study Design In a secondary analysis of 337 women with one to two prior losses assigned to placebo in a randomized controlled trial at four centers (2007–2012), cholesterol, low- and high-density lipoprotein cholesterol (HDL-C), and triglycerides were measured up to 6 months prepregnancy (time 0) and pregnancy up to 7 visits. Trajectories were created using linear mixed models. Multivariable logistic regression with adjustment for maternal characteristics and cholesterol was performed.Results Lipids decreased from prepregnancy to 4 to 5 weeks, followed by an increase, and were biphasic or triphasic depending on the lipid component. Between 4 and 8 weeks, for every 1-unit increase in HDL-C, there was a 22% decreased odds of loss <14 weeks (odds ratio: 0.78; 95% confidence interval: 0.60, 0.99) and 24% decreased odds of loss or preterm delivery 14 to <37 weeks (odds ratio: 0.76; 95% confidence interval: 0.60, 0.96).Conclusion There were no associations with other lipid components or other time points. An impaired rise of HDL-C early in pregnancy may signal maladaptation to pregnancy that is associated with pregnancy loss or preterm delivery.
Keywords: cholesterol; lipids; miscarriage; pregnancy loss; preterm delivery; spontaneous abortion